Hubungan antara Asupan Natrium, Kalium, Aktivitas Fisik dengan Hipertensi pada Perempuan Usia diatas 45 Tahun - Yaya Zanuba Maulidya; Umu Qonitun; Idcha Kusma Ristanti (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2024)
High blood pressure (hypertension) is a condition in which a person experiences an increase in blood pressure above normal which results in an increase in morbidity and mortality. The research design uses observational analytics with the "Cross Sectional" data collection method. The population in this study were women aged over 45 years in the Coastal Region of Tuban District, Tuban Regency with a total of 152 respondents, determined by the Simple Random Sampling technique. The analysis of this study used the Spearman Rank correlation statistical test. The results of the analysis between sodium intake and the incidence of hypertension showed a p value of 0.00, there was a significant relationship, the analysis between potassium intake and the incidence of hypertension showed a p value of 0.001, there was a significant relationship, and the analysis between physical activity intake and the incidence of hypertension showed a p value of 0.378, there was no significant relationship.Intake of sodium and potassium in women aged over 45 years has hypertension, and there is a relationship between sodium and potassium intake to the incidence of hypertension in the Coastal area of Tuban District, Tuban Regency, but there is no relationship between physical activity and the incidence of hypertension in the Coastal area of Tuban District, Tuban Regency. Keywords: Sodium, Potassium, Physical, Hypertensio